How Organizational Inefficiency Adversely Affects Number-of-employee Based Production Outputs - Forrest, Jeffrey Yi-Lin; Kara , Orhan; Augustin , Lua A.; Uzuner , Gizem; Liu , Jun (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2024)
This study uses an analytical approach to investigate the emerging disconnect between firm size and financial performance, as observed recently from a set of long-term data collected from U.S. public firms. By holding all organizational aspects of a firm constant, it confirms the validity of the old saying that the larger a firm is, the better chance it can secure advantages against rivals and the higher returns it can fetch. However, if the assumption about organizational aspects is removed, the present study shows that if a firm employs its assets to increase production output through hiring additional employees, then the consequently increased organizational inefficiency, as caused by interactions of the employees, will soon erase the expected increase in the output. Additionally, it is also shown, among other results, that when a firm hires additional human labor to meet the increasing market demand, the expected profit will decline after first reaching its maximum level. These results crystalize what has been speculated and what have been empirically observed. In the conclusion section, it is recommended that increasing a firm’s size, in terms of the number of employees, is not a realistic, efficient solution to meeting the challenge of increasing market demand. Instead, any genuine solution must satisfy the condition that it does not increase the organization’s inefficiency of the firm, such as increasing the magnitude of automation and/or digitization.